Integration of the Provus Discrepancy Model in assessing spatial flexibility in architectural design studios - Bekar, İrem; Kutlu, İzzettin (The Design journal, 2025)
Architectural education studios are significant spaces for assessing spatial use by students and faculty. This study aimed to evaluate user satisfaction in architecture faculty studios using the Provus Discrepancy Model. The findings revealed that while students expressed higher satisfaction, faculty members tended to be more critical in their evaluation of the spaces. This situation indicates that the needs and perceptions of different user groups may vary in the design of educational environments. The results underscore the importance of accommodating diverse user requirements in studio configuration, rather than adopting a one-size-fits-all approach. The study provides empirical evidence to inform the enhancement of flexibility in architectural education studios, contributing to the development of spaces better aligned with evolving pedagogical and practical needs.